Effect on Ca(OH)2 pretreatment to enhance biogas production of organic food waste - Junoh H.; Yip C.H.; Kumaran P. (Institute of Physics Publishing, 2023)
Calcium; Methane; Solubility; Anaerobic digestion process; Biomethane potential (BMP); Central composite designs; Chemical concentrations; COD solubilisation; Methane production; Optimized conditions; Response surface methodology; Anaerobic digestion; anoxic conditions; biogas; chemical oxygen demand; concentration (composition); design; digestibility; food; lime; methane; optimization; organic matter; solid waste; solubilization